Promoting Objectivity through Performance Assessment: The Case of Algerian EFL Master One Students' Tutorials at the University of Mohamed- Cherif Messaadia - Chaima ARAAR (My University, 2022)
Abstract The current study seeks to investigate the factors that can improve the objectivity of performance-based assessment with EFL students' tutorials in Algerian universities. It also aims to improve awareness among teachers and students about performance assessment and its impact on improving the student outcomes. The research opted for a mixed methods approach to collect both quantitative and qualitative data. Firstly, a web-based questionnaire was administered to 70 Master 1 students from the Department of English, at Souk-Ahras University. Secondly, an in-depth semi-structured interview was conducted with six teachers conveniently selected. The study findings revealed that an adequate scoring rubric that is shared among teachers in the same module and an explanation of task instructions are two elements that improve performance assessment objectivity. Such a kind of assessment is preferred by EFL teachers since it allows them to assess students' language competence and skills. In light of this, to gain greater objectivity while utilizing performance assessment, teachers must be mindful of the value of the scoring rubric and assessment tools.